The role of prostaglandin E2 in renal cell cancer development: future implications for prognosis and therapy. (November 2014) - Kaminska, Katarzyna; Szczylik, Cezary; Lian, Fei; Czarnecka, Anna M
ABSTRACT : COX-2 plays a crucial pathophysiological role in the development of renal cell cancer (RCC). Recently, it has been shown that COX-2 inhibition enhances the efficacy of immunotherapy and tyrosine kinase inhibitor-based treatment. At the same time, molecular analyses revealed particular contribution of a COX-2 product – prostaglandin E2 (PGE2) – in RCC development. PGE2 was shown to activate Akt/RGC2/RalA signaling cascade in RCC cells. It also demonstrated upregulation of the expression of HIF-1α and PI3K/Akt/mTOR signaling pathway. All together, these data suggest that targeted anti-PGE2 therapies may offer an interesting therapeutic option for RCC patients in the future.